Implementation of muslim personal financial management in the context of halal financial education - Maghfuroh, Nuril Laila; Qanita, Ariza; Muhammad, Zaydan (Journal of Halal Product and Research (JHPR), 2024)
Islam is a religion that is comprehensive in managing the lives of its people, including in the financial sector. Halal financial principles set out rules and guidelines that govern how Muslim individuals should manage their money in a manner that is in accordance with Islamic teachings which includes income, expenses, investments and financing. This research uses a descriptive qualitative method with a library research approach. The data collection method was carried out by searching for written library data sources and analyzing digital observations. This research aims to provide an overview of halal financial management so that Muslim individuals can gain skills and knowledge in managing finances according to Islamic principles. This is expected to increase halal financial literacy so that Muslims can achieve financial freedom.